Pemberdayaan Masyarakat dalam Pengembangan Kawasan Wisata Minapolitan di Desa Petalongan Kabupaten Indragiri Hulu - Yasir Yasir; Benny Heltonika; Muhammad Firdaus; Ismandianto Ismandianto; Noor Efni Salam (Universitas Mathla'ul Anwar Banten, 2021)
COMMUNITY EMPOWERMENT IN THE DEVELOPMENT OF MINAPOLITAN TOURISM AREAS IN PETALONGAN VILLAGE, INDRAGIRI HULU REGENCY. Petalongan village is located in the district of Pasir Penyu, Indragiri Hulu Regency-Riau Province. This village is still underdeveloped. Even though petalongan village has a lot of potential to be developed. In this case, the service activity aims to change people’s behavior in organizing, utilizing or managing their nature, traditions and culture to improve the community’s economy through the development of a tourist village minapolitan area. The targets of this service activity are BUMDes managers and PKK mothers. The service model uses Community Based Tourism (CBT), starting from mapping village potential, socialization, FGD, training, and mentoring. Based on the mapping and FGD, the potential of a village that can be developed is to make the village a minapolitan area for aquaculture-based tourism. The training activities focused on catfish and tilapia farming for BUMDes. Product development training is carried out aimed at supporting tourism and is also carried out in order to increase community understanding, attitudes and expertise in utilizing the potential of the village. This community service activity has had a positive impact on increasing community awareness and expertise in utilizing the existing potential by cultivating fish in the lake and having the will to develop the village as a tourist destination.